A postcolonial autopsy on Javanese identity through Campursari lyrics - Rahmat Setiawan; Armelia Nungki Nurbani; Sri Nurhidayah; Ani Asryan; Razanawati Nordin (NOTION: Journal of Linguistics, Literature, and Culture, 2023)
Campursari seems to reflect submissive identity, but in deconstructive perspective, the identity is chaotic space. By using postcolonial perspective, this research nails its analysis. The approach used in this research is library research with postcolonial approach. The data are the selected lyrics of Didi Kempot’s songs, they are Cidro, Tatu, Suket Teki, Pamer Bojo, and Sewu Kutho. The technique of data collection is documenting and the technique data analysis is interpretation. The result shows that Didi Kempot’s Campursari songs affirm the submissive way of loving. Cidro represents inferiority, Tatu represents surrender, Suket Teki represents inferiority, Pamer Bojo represents betrayal, and Sewu Kutho represents surrender. Those broken love defines Javanese identity which is seen submissive (dominated), but simultaneously, it also exposes a deconstructive point that loving is releasing, and releasing shows non-dominated side.